Construction, identification, and evaluation of dengue promotional campaign posters in a language classroom - Ahmed, Shabbir; Mohamad Ali, Afida; Rafik-Galea, Shameem; Mohamad Ali, Afiza; Mohd Zulkefli, Nor Afiah (Canadian Center of Science and Education, 2019)
Health promotional campaign as the practice of encouraging people to improve health has increased over the last decades in response to various health problems. This paper highlights strategies used by students to develop persuasive promotional campaign posters regarding the dengue health problem. Communication and media studies students were involved to show the combined results between the knowledge of health communication and the effective use of media in constructing an effective and persuasive health messages. A total of 56 students from two cohorts, i.e. twenty-five master’s students and thirty-one undergraduates were selected. Kurt Lewin’s model of action research was used to set the tasks: campaign objectives, information on dengue, themes/slogans to write the posters either by drawing or designing using a computer. The students were divided into groups where each group was monitored to record, check and evaluate their message writing performances. This study uses the Health Message Review Tool for data analysis which is grounded in the theories of Extended Parallel Process Model and Persuasion Hierarchy Effect. The findings revealed that the participants were able to construct, identify and evaluate major multi modal features in the dengue posters and persuasive elements which included: verbal texts, images, colours, graphic designs, metaphors, 1-sided and 2-sided message, firm conclusion and frames with more effective appeals. It was concluded that similar strategies may well be used in producing other campaign materials such as brochures, pamphlets, and billboards. The linguistic and pedagogic implications are also discussed at the end.